Renal ultrasound and voiding cystourethrogram in children with recurrent urinary tract infection (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Urinary tract infection (UTI) is common in children and vesicoureteric reflux (VUR) is a risk factor for the UTI. Renal ultrasound, voiding cystourethrogram (VCUG) and nuclear renal scanning are used to confirm VUR. Recent studies show that ultrasound has a low sensitivity and specificity for VUR. Aim of the study was to assess the findings of renal ultrasound and VCUG in recurrent urinary tract infection and presence of VUR.Methods: This cross-sectional study retrospectively reviewed 208 cases of children with recurrent UTI who had ultrasound and VCUG in at Patan Hospital during 2010 to 2015. Sensitivity and specificity of both tests were analysed. Amount of contrast required for VCUG with or without VUR was analysed.Results: Among the 209 patients with recurrent UTI, 51 (24.51%) had VUR and 157 (75.48%) were normal. In ultrasound, 196 cases (94.2%) were normal, 11 cases (5.3%) had mild hydronephrosis and 1 (0.5%) had moderate hydronephrosis. VUR cases needed more amount of contrast medium than normal patients while performing VCUG.Conclusions: Ultrasound alone is not diagnostic of VUR and VCUG is required to confirm diagnosis. Mire amount of contrast volume is required in VUR cases than no VUR.